Implementasi Konsep “Unity in Balance” pada Desain Interior Pusat Aktivitas Komunitas Xian You di Surabaya - Steffi Alyssandtea Purwanto; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
The spread of Chinese ethnic in Indonesia made the residents of Xian You immigrate to Indonesia to earn a living. These immigrants then created a Xian You community that aims to cultivate fellow Xian You descendants, educate, and help each other. Today, this community is still standing and has activities that need to be well accommodated with an interactive and educational facility. Application three forms of culture which are the values, order of activity, and spatial organization, initiates the concept of Unity in Balance. Implementation of this concept is shown by using interactive educational media, interior elements that reflects Chinese culture and also a touch of local culture. Space organization used is the implementation of the traditional Chinese house organization. Implementation of this concept is expected to accommodate community activities, attract young generation of the community, and to be the existence proof of Chinese ethnic in Surabaya